2017
DOI: 10.5999/aps.2017.44.5.384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remote Ischemic Conditioning Methods on Ischemia-Reperfusion Injury in Muscle Flaps: An Experimental Study in Rats

Abstract: BackgroundThe aim of this study was to investigate the effects of remote ischemic conditioning on ischemia-reperfusion injury in rat muscle flaps histopathologically and biochemically.MethodsThirty albino rats were divided into 5 groups. No procedure was performed in the rats in group 1, and only blood samples were taken. A gracilis muscle flap was elevated in all the other groups. Microclamps were applied to the vascular pedicle for 4 hours in order to achieve tissue ischemia. In group 2, no additional proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A histologic examination can show myocyte injury directly, including the integrity of the cell membrane, gaps within the cell, and staining intensity [30,32]. In previous studies, morphological changes due to I/R was shown [33][34][35]. In this study, we used histopathological examination to show I/R injury and the effect of fullerenol on I/R injury of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…A histologic examination can show myocyte injury directly, including the integrity of the cell membrane, gaps within the cell, and staining intensity [30,32]. In previous studies, morphological changes due to I/R was shown [33][34][35]. In this study, we used histopathological examination to show I/R injury and the effect of fullerenol on I/R injury of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry based analysis of kidney biopsies as described here revealed several noticeable features at a molecular level that could potentially be exploited to further optimise the RIC regimen, although recent studies have not pointed to positive clinical effects of RIC [ 15 , 24 ]. We observed accumulated muscle proteins in kidney tissue from RIC patients, most likely derived from muscle injury inflicted by a repeated mechanical obstruction to the arterial flow in the leg opposite the transplant using a tourniquet or to the pressure of the tourniquet on the muscles [ 25 ]. Higher levels or myoglobin and troponin in the RIC group in kidney tissue may be attributed to the response of muscle to the induction of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…IPOC has been shown to produce protective effects on prolonged ischaemia-induced muscle damage through similar mechanisms to that of IPC [ 16 ]. IPOC may also have effects on ischaemic limbs that have not directly received IPOC treatment, otherwise known as remote effects [ 17 ]. However, the application of IPOC in sports has been scarce, and whether IPOC could reduce EIMD and DOMS remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%